Cyclophosphamide induces ovarian granulosa cell ferroptosis via a mechanism associated with HO-1 and ROS-mediated mitochondrial dysfunction - Hui Chen; Ping Nie; Jingling Li; Yongqi Wu; Bo Yao; Yabing Yang; Gendie E. Lash; Ping Li (Journal of Ovarian Research, 2024)
Abstract Abnormal granulosa cell (GC) death contributes to cyclophosphamide (CTX) induced primary ovarian insufficiency (POI). To investigate the contribution of GCs to POI, gene profiles of GCs exposed to CTX were assessed using RNA-Seq and bioinformatics analysis. The results showed the differentially expressed genes (DEGs) were enriched in the ferroptosis-related pathway, which is correlated with upregulated heme oxygenase 1 (HO-1) and downregulated glutathione peroxidase-4 (GPX4). Using CTX-induced cell culture (COV434 and KGN cells), the levels of iron, reactive oxygen species (ROS), lipid peroxide, mitochondrial superoxide, mitochondrial morphology and mitochondrial membrane potential (MMP) were detected by DCFDA, MitoSOX, C11-BODIPY, MitoTracker, Nonylacridine Orange (NAO), JC-1 and transmission electron microscopy respectively. The results showed iron overload and disrupted ROS, including cytoROS, mtROS and lipROS homeostasis, were associated with upregulation of HO-1 and could induce ferroptosis via mitochondrial dysfunction in CTX-induced GCs. Moreover, HO-1 inhibition could suppress ferroptosis induced GPX4 depletion. This implies a role for ROS in CTX-induced ferroptosis and highlights the effect of HO-1 modulators in improving CTX-induced ovarian damage, which may provide a theoretical basis for preventing or restoring GC and ovarian function in patients with POI.